ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL, DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Perusahaan Property And Real Estate Yang Terdaftar Di Bursa Efek Indonesia Untuk Tahun 2010-2013) - Yanuar Cristie; Fuad Fuad (Diponegoro Journal of Accounting, 2015)
This study aims to analyze and provide empirical evidence about the influence of Profitability, Growth Opportunities, Tangibility, Cost of Financial Distress, and Non-Debt Tax Shield against Capital Structure , which is moderated by the size of the company. Several previous studies have shown varying results. To obtain valid results, the testing of each variable based on the hypothesis that built. The samples used were selected by purposive sampling method. The study population was 52 Property and Real Estate company that went public in Indonesia Stock Exchange . After reduction with multiple criteria, 30 companies identified as samples. Year observation period is 2010-2013, so that the sample used is 120 samples. Multiple regression was used to test the hypothesis, and Residual Test is used to test the moderating variables. The results showed that Profitability, Tangibility, Cost of Financial Distress, and Non- Debt Tax Shield affect the Capital Structure. While the Growth Opportunity does not affect the use of debt.